Cross-cultural adaptation and validation of the Urinary Incontinence Scale After Radical Prostatectomy for the Brazilian context - Luciana Regina Ferreira da Mata; Cissa Azevedo; Aline Carrilho Menezes; Sabrina de Cássia Chagas; Lívia Cristina de Resende Izidoro; Fabrícia Eduarda Baia Estevam; Tânia Couto Machado Chianca (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To translate, adapt, and validate the Urinary Incontinence Scale After Radical Prostatectomy for Brazil. Method: Methodological study: cross-cultural adaptation (translation, synthesis, back translation, expert committee (n=25), pre-testing (n=40) and presentation to original authors) and evaluation of measurement properties (n=80). Data were collected between January 2018 and February 2019 in an oncology unit. The calculated measurement properties: structural validity, hypothesis testing, criterion validity and reliability. Results: The Brazilian version was called Escala de Incontinência Urinária Pós-Prostatectomia Radical. One item was excluded due to low factor loading (0.322). A significant correlation was identified between the total score of the scale and instruments applied (p<0.001). Incontinent men had higher scores on the total scale in relation to continents (p<0.001). Cronbach's alpha was 0.94 and composite reliability was 0.97. Conclusion: The Brazilian version was considered valid and reliable for the assessment of urinary incontinence in prostatectomized patients.